Hydrogen production from homocyclic liquid organic hydrogen carriers (LOHCs): Benchmarking studies and energy-economic analyses. (1st July 2021) - Kwak, Yeonsu; Kirk, Jaewon; Moon, Seongeun; Ohm, Taeyoon; Lee, Yu-Jin; Jang, Munjeong; Park, La-Hee; Ahn, Chang-il; Jeong, Hyangsoo; Sohn, Hyuntae; Nam, Suk Woo; Yoon, Chang Won; et al.
Graphical abstract: Highlights: Affordable homocyclic LOHCs can easily store H2 with a storage capacity of 6–8 wt% at ambient conditions. Benchmarking studies for homocyclic LOHC dehydrogenation were conducted. Model Pt/γ-Al2 O3 catalyst and physicochemical properties of representative homocyclic LOHCs were studied. Energy analysis and economic assessment in maritime transport scenarios were performed. Abstract: The construction of a cost-effective hydrogen infrastructure is needed to perpetuate the deployment of the hydrogen economy. Liquid organic hydrogen carriers (LOHCs), generally possessing a hydrogen storage capacity of 6–8 wt%, can store a large volume of hydrogen for an extended period at ambient temperature and pressure. LOHCs are also highly compatible with conventional petroleum production and transport infrastructure. The proper selection among strong LOHC candidates is of paramount importance; hence, benchmarking studies are required for a fair comparison. Herein, the dehydrogenation characteristics of different homocyclic (Cx Hy -) LOHCs are studied in a high-throughput screening system with continuous fixed-bed reactors. Four homocyclic LOHCs, including methylcyclohexane, hydrogenated biphenyl-based eutectic mixtures, perhydro-monobenzyltoluene, and perhydro-dibenzyltoluene, are dehydrogenated using a 0.5 wt% Pt/Al2 O3 heterogeneous catalyst under the identical test protocol for comparative analysis. We further discuss post-mortem analyses on the used catalyst, physicochemical properties of LOHCs, energy analysis, and economic assessment of a maritime transport scenario for each LOHC, suggesting a future strategy to promote the practical use of homocyclic LOHCs.